(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Various imaging tools are utilized for the quantitative assessment of renal function in clinical practice. Integration of Doppler ultrasonography and renal scintigraphy might be invaluable for different aspects of renal evaluation. However, the relationship between these modalities remains incompletely defined. In this prospective observational study, multiple linear regression analyses were performed to evaluate the predictive value of Doppler parameters and scintigraphy derived estimations in both kidneys. For the right kidney, glomerular filtration rate was significantly predicted by resistive index (β = –0.448, p = 0.036) and relative perfusion (β = 0.535, p = 0.001), with an overall model fit of R² = 0.533 (p = 0.001). For the left kidney, glomerular filtration rate was strongly predicted by relative perfusion (β = 0.787, p < 0.001), with an overall model fit of R² = 0.700 (p < 0.001). In conclusion, Doppler indices alone do not reliably predict renal perfusion, underscoring the complementary rather than interchangeable role of Doppler and scintigraphy. Integrated use of both modalities enhances renal functional assessment and may improve diagnostic accuracy in patients with suspected renal impairment. Bangladesh J. Nuclear Med. 28(2): 241-246, July 2025